(untitled) (Palíndromo, 2024)
The aim of this study is to argue that Priam is the main character in the paintings of the ransom of Hector and that the painters, by focusing on him, represented his tragedy. To achieve this aim, six paintings considered the most dramatic were selected, which are analyzed based on the visual narrative, considering the composition, gestures, and postures. Since Homer’s Iliad served as an inspiration to painters, it is presented how Homer conceived this scene, as well as Aristotle’s understanding of tragedy, to highlight the dramatic character of the pictorial tradition and its specificities.